(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The goal of this research was to evaluate where selenium nanoparticles impact the activity of antibodies in immunized lambs with foot and mouth vaccines by modulating the immune system. Materials and Methods: Two groups of lambs of 3–4 months of age were injected with 1 ml of ARRIAH-VAC vaccine intramuscularly in the neck, five Lambs were given selenium nanoparticles (size 100 nm) oral administration of selenium nano dose of 0.1 mg/kg of body mass once every day for sixty days considered as group one (G1) while the other five used as control Group 2 (G2). Results: This resulted in the establishment of an immune response, as evidenced by a rise in antibody titer in the blood using the ELISA test for three serotypes A, O, and Asia 1, when selenium nanoparticles were given orally at a dose of 0.1 mg/kg body weight after immunization, we noticed a significant (p >0:05) selenium nano group increase in IgG response in all immunized groups in contrast to lambs that had only received the foot-and-mouth disease vaccine Conclusion: We have demonstrated that selenium nanoparticles administered orally significantly enhance immune responses while also increasing body weight. Adv. Vet. Anim. Res., 11(2): 367-375, June 2024 http://doi.org/10.5455/javar.2024.k785